Low-Level Mouse DNA in Conditioned Medium Generates False Positive Cross-Species Contamination Results in Human Organoid Cultures - Bohm, Margaret S.; Dame, Michael K.; Boyd, Joseph; Su, Kevin; Wu, Angeline; Attili, Durga; Chu, Vi; Colacino, Justin A.; Spence, Jason R. (Frontiers in Cell and Developmental Biology, 2020)
Cell line authentication is critical for preventing the use of mixed or misidentified cell lines in research. Current efforts include short tandem repeat (STR) analysis and PCR-based assays to detect mixed species cultures. Using PCR analysis with mouse-specific primers, we identified contaminating mouse DNA in growth factor conditioned medium (CM derived from the L-WRN cell line (L-WRN CM), as well as in human organoid cultures maintained in the L-WRN CM. DNA isolated from L-WRN CM matched the L-WRN cell signature by STR analysis. Organoid lines that were positive for murine DNA by PCR were further analyzed via bulk RNA-sequencing and transcripts were aligned to the human and mouse genomes. RNA analysis failed to detect mouse-specific gene expression above background levels, suggesting no viable murine cells were present in the organoid cultures. We interpret our data to show conclusive evidence that mouse cell-derived CM can be a source of contaminating murine DNA detected in human organoid cultures, even though live, transcriptionally-active murine cells are not present. Together, our findings suggest that multiple methods may be required to authenticate human organoid or cell lines and urges cautious interpretation of DNA-based PCR cell line authentication results.